Espaço, corpo e escrita em Al Berto: á procura do vento num jardim d'agosto - Gustavo Cerqueira Guimaraes (2005)
This present work proposes a discussion about the presence of the space, the body and the writing in À procura do vento num jardim dagosto, the book that debuts the portuguese poet Al Berto, which was published in 1977 and rewritten in 1987. It situates the writer and his work in the contemporary portuguese literature, also remarking the autobiographic aspects and the dialog with other semiotics systems. It compares those two differents editions and the peculiarities of the narrative, which brings as a central theme the subject-body. It analyzes the places where the subject-body enunciates its own writing and the city spaces, in which stands out the expression of sexuality.